Investigating Students’ Speaking Difficulties and Finding Alternative Solutions at Islamic Affiliated Junior High Schools - Salim, Agus; Jumadil, Jumadil; Suryati, Suryati (Journal of Language and Literature Studies, 2023)
In the realm of English for Specific Purposes (ESP), the cultivation of speaking skills demands specialized learning techniques and models. This particular study embarked on the mission of tackling the speaking challenges encountered by students in Islamic-affiliated junior high schools in West Lombok, Indonesia. Employing a qualitative approach, the researchers harnessed interviews and observations as their research methods. The investigation uncovered a spectrum of hurdles faced by students, including a restricted vocabulary, a dearth of fluency, and an apprehension of making mistakes. In response to these challenges, the researchers strategically employed interviews to augment vocabulary and speaking proficiency, leveraging humor and jokes to foster a relaxed and enjoyable learning atmosphere. The outcomes were promising, showcasing heightened engagement and motivation among students to actively participate in speaking exercises during lessons. The discernible improvement in the students' speaking skills was multifaceted, encompassing advancements in vocabulary, fluency, and overall confidence. Notably, the students not only demonstrated progress but also exhibited positive attitudes towards the teaching methodology employed, describing it as both enjoyable and effective. This study underscores the efficacy of integrating interviews and humor as potent tools in addressing speaking difficulties. It underscores the paramount importance of crafting an engaging and pleasurable learning milieu, emphasizing that such an environment contributes significantly to the enhancement of students' speaking skills. Ultimately, this research sheds light on the transformative impact of innovative teaching approaches within the realm of ESP, offering a compelling case for the adoption of these strategies to foster improved speaking abilities among students.